Repurposing fish waste into valuable products - Mumbai Archive Project Team (Jio Institute, 2024)
Repurposing fish waste into valuable products and resources has not only minimized waste generation, reduced environmental pollution, and created economic opportunities—particularly for Koli women—but it has also contributed to a more sustainable and circular economy.